Proses Permesinan Non Konvensional Dengan Abrasive Water Jet Machining Untuk Material Keramik - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Sisworo (Teknis, 2016)
The process of cutting material is reshaped by cutting. Non conventional cutting process is needed to overcome the shortcomings in the previous process is conventional. For ceramic type material that has properties; hard, strong and setabil at high temperatures, but brittle and easily broken or cracked. Emphasis on the brittle material resulted in local crack follow devormasi elastic. With the abrasive water jet machining (AWJM) technology is cutting the material with tap 4.2 bar mixture of 70% water and 30% abrasive able to overcome the shortcomings of conventional process.Keywords: AWJM, cutting of ceramic materials